Monte Carlo Comparison of Proton and Helium-ion Minibeam Generation Techniques - Schneider, Tim; De Marzi, Ludovic; Patriarca, Annalisa; Prezado, Yolanda (Frontiers in Physics, 2021)
Proton minibeam radiation therapy (pMBRT) is a novel therapeutic strategy that combines the normal tissue sparing of submillimetric, spatially fractionated beams with the improved dose deposition of protons. In contrast to conventional approaches which work with comparatively large beam diameters (five millimetres to several centimetres) producing laterally homogeneous fields, pMBRT uses submillimetric minibeams to create a distinct spatial modulation of the dose featuring alternating regions of high dose (peaks) and low dose (valleys). This spatial fractionation can increase the tolerance of normal tissue and may allow a safe dose escalation in the tumour. Important quantities in this context are the valley dose as well as the peak-to-valley dose ratio (PVDR). Creating submillimetric proton beams for clinical applications is a challenging task that until now has been realised with mechanical collimators (metal blocks with thin slits or holes). However, this method is inherently inefficient, inflexible and creates undesirable secondary neutrons. We therefore recently proposed a method for obtaining clinical minibeams using only magnetic focussing. In this study, we performed Monte Carlo simulations in order to compare minibeams generated using the new method of magnetic focussing with two techniques involving mechanical collimators (collimator and broad beam irradiation, collimator and pencil beam scanning). The dose deposition in water was simulated and dosimetric aspects (beam broadening, depth-dose profiles, PVDR and Bragg-peak-to-entrance dose ratio [BEDR]) as well as irradiation efficiencies were evaluated. Apart from protons, we also considered helium ions which, due to their reduced lateral scattering and sharper Bragg peak, may present a promising alternative for minibeam radiation therapy. Magnetically focussed minibeams exhibited a 20 to 60 times higher PVDR than mechanically collimated minibeams and yielded an increase in irradiation efficiency of up to two orders of magnitude. Compared to proton minibeams, helium ion minibeams were found to broaden at a slower rate and yield an even higher PVDR (at the same minibeam spacing) as well as a more favourable BEDR. Moreover, the simulations showed that methods developed for proton minibeams are suitable for the generation of helium ion minibeams.